2020
DOI: 10.3310/phr08020
|View full text |Cite
|
Sign up to set email alerts
|

A weight management programme for fathers of children aged 4–11 years: cultural adaptation and the Healthy Dads, Healthy Kids UK feasibility RCT

Abstract: Background More men than women in the UK are living with overweight or obesity, but men are less likely to engage with weight loss programmes. Healthy Dads, Healthy Kids is an effective Australian weight management programme that targets fathers, who participate with their primary school-aged children. Behavioural interventions do not always transfer between contexts, so an adaptation of the Healthy Dads, Healthy Kids programme to an ethnically diverse UK setting was trialled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…Similar to this study, they engaged representatives of the target population in interviews and focus groups, in addition to formative data from other ongoing studies to inform their adaptation of HDHK. The resulting adaptations included changes in the recruitment and follow-up procedures, program delivery and program content, primarily at a surface structural level [44]. After two feasibility trials of the adapted HDHK-UK program, the researchers concluded that despite the program being delivered with high fidelity and well received among participants, there were significant challenges in recruiting overweight or obese men and low follow up rates, resulting in the adapted program not being evaluated in an efficacy trial.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, they engaged representatives of the target population in interviews and focus groups, in addition to formative data from other ongoing studies to inform their adaptation of HDHK. The resulting adaptations included changes in the recruitment and follow-up procedures, program delivery and program content, primarily at a surface structural level [44]. After two feasibility trials of the adapted HDHK-UK program, the researchers concluded that despite the program being delivered with high fidelity and well received among participants, there were significant challenges in recruiting overweight or obese men and low follow up rates, resulting in the adapted program not being evaluated in an efficacy trial.…”
Section: Discussionmentioning
confidence: 99%
“…Consultation methods undertaken to inform the intervention design process varied across studies, including focus groups, workshops, survey data, and various patient and public involvement activities. Of the nine studies that consulted men, four specifically reported engaging with lower socioeconomic groups 99–102 . In the cultural adaptation of the Healthy Dads Healthy Kids intervention for men and children from low‐income Hispanic communities in the United States, family members participated in focus groups, online surveys, and interviews with findings reviewed by stakeholder experts to inform the adaptation 101 .…”
Section: Resultsmentioning
confidence: 99%
“…The group encouraged the research team to be fully open about the challenges faced in delivering the HDHK programme and the research study." [28] Discussion and conclusions Comment on the extent to which PPI influenced the study overall. Describe positive and negative effects.…”
Section: Study Resultsmentioning
confidence: 99%